Expanding the knock/emissions limits for the realization of ultra-low emissions, high-efficiency heavy-duty natural gas engines - Rodriguez Rueda, Juan Felipe, author; Olsen, Daniel B., advisor; Windom, Bret, committee member; Baker, Daniel, committee member; Quinn, Jason, committee member (Colorado State University. Libraries, 2023)
Heavy-duty on-highway natural gas (NG) engines are a promising alternative to diesel engines to reduce greenhouse gas and harmful pollutant emissions if the limitations (knock and misfire) for achieving diesel-like efficiencies are addressed. This study shows innovative technologies for developing high-efficiency stoichiometric, spark-ignited (SI) natural gas engines. To develop the base knowledge required to reach the desired efficiency, a Single Cylinder Engine (SCE) is the most effective platform for acquiring reliable and repeatable data. An SCE test cell was developed using a Cummins 15-liter six-cylinder heavy-duty engine block modified to fire one cylinder (2.5-liter displacement). A Woodward Large Engine Control Module (LECM) is integrated to permit real-time advanced combustion control implementation. Fixed location of 50% burn and Controlled End Gas Auto-Ignition (C-EGAI) were used to define the ignition timing. C-EGAI allows operation with an optimized fraction of end gas auto-ignition combustion. Intake and exhaust characteristics, fuel composition, and exhaust gas recirculated substitution rate (EGR) are fully adjustable. A high-speed data acquisition system acquires in-cylinder, intake, and exhaust pressure for combustion analysis. Further development includes advanced control methodologies to maintain stable operation and higher dilution tolerance. Controlled end-gas autoignition (C-EGAI) is used as a combustion control strategy to improve efficiency. A Combustion Intensity Metric (CIM) is used for ignition control while operating the engine under C-EGAI. During the baseline testing of the developed SCE test cell, effective control of intake manifold pressure, exhaust manifold pressure, engine equivalence ratio, speed, torque, jacket water temperature, and oil temperature was demonstrated. The baseline testing shows reliable and consistent results for engine thermal efficiency, indicated mean effective pressure (IMEP), and coefficient of variance of the IMEP over a wide range of operating conditions. High Brake Thermal Efficiency (BTE) was achieved using improved hardware and a high EGR rate. Due to the correlation of CIM to the fraction of EGAI (f-EGAI), CIM was used as the reference variable to implement C-EGAI. Achieving conditions of C-EGAI allowed for the utilization of high EGR at high IMEP without inducing knock. The operation of the engine under these conditions showed peak brake thermal efficiency above 46% using an EGR ratio of 30% The work described proves the concept of using new and innovative control algorithms and CFD-optimized combustion chamber designs, allowing ultra-high efficiency and low emissions for NG ICE's heavy-duty on-road applications.
Keywords: heat release; natural gas; end gas auto-ignition; single cylinder engine; heavy-duty